Energy Management in Energy Intensive Industries - Recommended Technical & Managerial Actions and a Delphi Study - Vilson Roiz Gonçalves Rebelo da Silva; Eduardo de Freitas Rocha Loures; Edson Pinheiro de Lima; Luiz Antonio Belinaso (Brazilian Archives of Biology and Technology, 2023)
Abstract This paper presents the proposition of a set of technical and managerial actions recommended for the management of energy in industry. Economic, environmental, political and social aspects have been putting pressure on the whole society for a more conscious and efficient use and consumption of energy in its diverse forms. Energy-intensive industries show a high energy consumption, they work with processes in severe temperature conditions, residual dissipation of heat and flux of not used residues, always being subject to great environment risks. These large-sized companies offer great opportunities for making energy more efficient, use of co-generation and various other possibilities for a better management and improvement of energetic performance. The research is characterized as quali-quantitative, exploratory and descriptive, presenting a statistical analysis for the questionnaire answers. The energy management practices refer to procedures used for dealing with energetic issues. In function of the interdisciplinary aspect of energy management in the industry, the management practices can be better understood with technical and managerial continuous or frequent actions. A Delphi study for verification of the validity of the proposed technical and managerial actions was carried out together with academia and industry specialists. The results show a favorable positioning, confirmed by a reliability rate among suitable evaluators (IRR - Inter Rater Reliability). The set of technical and managerial actions is made up of reference elements for creation, organization and conduction of an energy management system in the industry.